Madurese Christian: In Search of Christian Identity within Muslim Society - Akhmad Siddiq (Al-Jami'ah Research Centre, 2019)
In many discussions and conversations with Muslim Madurese I often heard common belief that none of Madurese individuals embraces Christianity. They mostly conceive that almost one hundred percent of Madurese people are Muslim while Christian people living in Madura are generally non-Madurese. It might be right but the fact shows that some of the Madurese have embraced Christianity, besides Madurese Christian community in Sumber Pakem East Java which is practicing Christianity for more than four generations. The ignorance of Madurese Muslim toward Christian population, especially Madurese Christian in Madura, appear because of less interaction between Muslim and Christian on the one hand and social worries of Madurese Christians to express their identity on the other. This paper aims to describe the existence of Madurese Christians, examine how they survive inside and outside Madura island, and how they interact with Madurese Muslims. It also attempts to elucidate cultural connection between ethnicity (of Madurese) and religiosity (of Christian).[Dalam perlbagai diskusi dan perbincangan dengan orang Madura, seringkali terdengar pernyataan bahwa tidak ada orang Madura yang memeluk Kristen. Dipercaya bahwa 100 % orang Madura adalah muslim, sedangkan orang Kristen di Madura adalah bukan orang Madura. Hal ini mungkin benar, namun realitasnya berkata bahwa ada sekolompok orang Madura memeluk Kristen beberapa generasi dan tinggal di Sumber Pakem, Jawa Timur. Ketidaktahuan ini disebabkan oleh minimnya interaksi antara Madura muslim dan Kristen disatu sisi, dan di sisi yang lain karena adanya kegamangan kelompok Madura Kristen untuk menunjukkan identitasnya pada publik. Artikel ini menjelaskan keberadaan orang Madura Kristen dan bagaimana mempertahankannya dan berinteraksi dengan muslim, baik di dalam maupun luar Pulau Madura. Artikel ini juga mengeksplorasi hubungan kultural antara etnisitas (Madura) dengan agama (Kristen).]